Dynamic Modelling and Logistics Planning in Business Process Re-engineering (BPR) - Wiesław STANIUK; Michał STANIUK; Norbert CHAMIER-GLISZCZYNSKI (Communications of International Proceedings, 2021)
Managing changes in the supply chain, resulting from the necessity to adapt them to the changing market situation, is a challenge for many companies, often burdened with high risk. Time pressure, which is omnipresent in dynamic processes, as well as the applied planning methods, do not provide organizations with the efficiency and expected speed of introducing changes. The process of adapting enterprises to changes is a consequence of ongoing processes of transforming the economy in compliance with the Industry 4.0 concept (UNITY, 2020; Przemysł 4.0, 2021). This paper presents an innovative logistics planning method – the Logistics Planning LP9A. The logistical planning method presented herein is based on the results of our own research on the implementation of a process-integrated and computer-aided method with dedicated LP9A software. The LP9A logistics planning method presented in this publication, which is part of the BPR method used in practice since 2010, allows for a complete, system-oriented planning that takes into account dynamic changes in the supply chain, including those specific and characteristic to the disruption period resulting from the impact of the COVID-19 pandemic on the global economy.
Keywords: Supply chain; supply chain modelling; supply chain simulation; logistic planning; business process reengineering; management